2008
DOI: 10.1371/journal.pone.0002751
|View full text |Cite
|
Sign up to set email alerts
|

The Male Sex Pheromone of the Butterfly Bicyclus anynana: Towards an Evolutionary Analysis

Abstract: BackgroundFemale sex pheromones attracting mating partners over long distances are a major determinant of reproductive isolation and speciation in Lepidoptera. Males can also produce sex pheromones but their study, particularly in butterflies, has received little attention. A detailed comparison of sex pheromones in male butterflies with those of female moths would reveal patterns of conservation versus novelty in the associated behaviours, biosynthetic pathways, compounds, scent-releasing structures and recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
268
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(280 citation statements)
references
References 72 publications
8
268
2
2
Order By: Relevance
“…Alternatively, premating social experience could alter signal weighting. B. anynana, like many animals, uses both olfactory and visual signals to assess mate quality (16,17,34,35). Sex pheromone production is variable in male B. anynana and changes with age (35,36).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, premating social experience could alter signal weighting. B. anynana, like many animals, uses both olfactory and visual signals to assess mate quality (16,17,34,35). Sex pheromone production is variable in male B. anynana and changes with age (35,36).…”
Section: Resultsmentioning
confidence: 99%
“…We first removed any peak smaller than 10 ng, to homogenize the detectability of compounds between samples and to permit the identification of all selected peaks. Despite the ability of GC-EAD to detect the presence of olfactory receptors for chemicals present in minute amounts, the B. anynana MSP was shown to be formed by the most abundant, male-specific and repeatable compounds [25]. We thus selected the compounds on average more than five times more abundant in males than in females and present in at least two out of three sampled males.…”
Section: Materials and Methods (A) Samplingmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that male sex pheromone (MSP) plays a key role in mate choice in the model species Bicyclus anynana [25][26][27]. After landing behind a female, B. anynana males flicker their wings and erect their androconial hair, probably favouring the dissemination of MSP at short range [25]. Therefore, we postulated that selection on differentiation in the sex pheromone composition has produced recurrent RCD in this butterfly genus.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Androconia were often overlooked in early taxonomic work on Bicyclus, but as species numbers increased and identification became more challenging they gradually gained importance in species descriptions. More recently the pheromonal functions of Bicyclus androconia (Nieberding et al, 2008) and their links to speciation process (Bacquet et al, 2015) have been the focus of new research.…”
Section: Introductionmentioning
confidence: 99%